PERAN AGAMA ISLAM DALAM MENGHADAPI ERA MATERIALISME - Rasyid, Abdur (Jurnal Ilmiah Al-Hadi, 2019)
In various corners, there is no discussion other than a matter of improving the economic level, the fulfilment of lust and passion. Adults and children make no difference. We are aware that humans need collateral and support in their material aspects. In the Scriptures, we are reminded of the importance of the value of property and material potential in encouraging many charities. However, we must not forget that the economic facilities that we want to control are all just roads, not end. The purpose of using these means is to defend and fight for great and noble values. Most people do not know the purpose of their existence. They live in vain amid the stuffy life. Some of them live for charity and struggle. Some of them live playfully, far from seriousness, and as if they have no purpose. They should take the straight path of life in His direction.